Learning Assessment in Higher Education: academic contributions for Spanish-speaking teachers - Maldonado Fuentes, Ana Carolina (2023)
The objective of this study was to investigate Learning Assessment as an integral part of the professional knowledge required for educators to assess whether educational objectives have been met at the tertiary level. A comprehensive literature review was conducted, analyzing academic sources within the Web of Science database from 2017 to 2021, resulting in a collection of 56 papers in Spanish. Following the application of rigorous double-blind inclusion and exclusion criteria, content analysis was performed on 17 publications that encompassed a range of approaches. Notably, prevalent among these were the concepts of formative assessment, assessment for learning, and the incorporation of feedback in pedagogical innovations. However, more robust theoretical frameworks based on concep-tual and historical foundations were less frequently encountered. Consequently, this study marks a departure from the conventional perspective on traditional learning assessment, signaling a fresh approach to enhancing assessment literacy among Spanish-speaking educators in the domain of Higher Education.